2021
DOI: 10.3390/ijerph18136880
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Older Adults’ Perception of High-Density Housing Neighbourhoods in Singapore: Multi-Sensory Perspective

Abstract: Associated sensory and cognitive declines progress with ageing and profoundly impact the daily living and quality of life of older adults. In the context of an increased ageing population globally, this paper outlines an exploratory study of socio-sensory properties of two high-density housing neighbourhoods in Singapore and the ways senior local residents perceive their familiar built environments. This study employed exploratory on-site exercises with 44 student researchers (including sensory photo-journeys,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Previous studies have proved that there is no significant difference between using photos to replace landscapes as the evaluation of the space [15,16], and using photos even has advantages of high efficiency and cost savings and the ability to compare and evaluate multiple spaces at the same time. This method has been widely used in related research [17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have proved that there is no significant difference between using photos to replace landscapes as the evaluation of the space [15,16], and using photos even has advantages of high efficiency and cost savings and the ability to compare and evaluate multiple spaces at the same time. This method has been widely used in related research [17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…Zdravko Trivic conducted a multisensory assessment of older people in a high-density residential area and found that the sensory richness of the community influences the daily behaviour of older residents and ultimately residential well-being, and that the findings provide sufficient information to support the redesign of the community [24].…”
Section: Theoretical Frameworkmentioning
confidence: 99%